Substantial N2O emissions from peat decomposition and N fertilization in an oil palm plantation exacerbated by hotspots - Oktarita, Satria; Hergoualc'h, Kristell; Anwar, Syaiful; Verchot, Louis V (Environmental research letters, 2017)
It is unclear to what extent emissions of nitrous oxide (N2O) from drained histosols in the tropics may contribute to the atmospheric burden of greenhouse gases. In particular, there is a critical need to elucidate their magnitude in oil palm plantations on these soils. We examined spatio-temporal variations of N2O emissions from peat decomposition and nitrogen (N) fertilization in a plantation trial in Sumatra, which included three application rates: 0 (N0), 153 (N1) and 306 (N2) kg N ha−1 y−1. The spatially stratified sampling design distinguished the area around the palms which received fertilizer (9% of the surface) from the rest of the plot which was unfertilized. Annual emissions were substantial with rates of 22.1 ± 5.7, 12.8 ± 2.7 and 26.6 ± 5.7 kg N2O-N ha−1 in the N0, N1 and N2 treatments, respectively. These equal 9.3 ± 2.4, 5.4 ± 1.1 and 11.2 ± 2.4 Mg CO2eq ha−1 y−1, or 5-10 times emission rates in natural peatland forest. The site exhibited two persistent hotspots located in the unfertilized zone, contributing 33 and 46% of annual emissions in N0 and N2 while representing only 10% of the area sampled. The response of emissions to fertilization was exponential but restricted to the small N application area. At the plot scale and over the year, the impact of fertilized-induced emissions was minimal due to the prevalence of emissions from peat decomposition. Annual rates among treatments were similar when discarding the contribution of hotspots to evaluate N addition effect. High N2O emissions from peat decomposition in the tropics tend to be common within the restricted existing literature; which is in contrast with most recent IPCC emission factors. Our results emphasize the importance to integrate N2O emissions in greenhouse gas budgets of plantations on peat, despite the predominance of CO2 in total emissions.